WATER DEFICIT AND SALINITY STRESS INDUCED ALTERATIONS IN THE MORPHOLOGICAL CHARACTERISTICS OF OENOTHERA BIENNIS L. GROWN IN WESTERN HIMALAYAN REGION - Sikha, Kumari (International Journal of Research -GRANTHAALAYAH, 2025)
The present study aimed at determining the morphological response of Oenothera biennis L. under water stress and salinity stress caused by altering climatic conditions in the present scenario. Water deficit and salinity stress are one of the major abiotic stress factors show negative impact on growth, development and yield on different agricultural activities .Thus demands the need of developing water deficit and salt tolerant plant varieties. Oenothera biennis L. is one of the important medicinal plant with several medicinal properties, but information related to morphological response which helps in determining the level of water and salinity stress tolerance in Oenothera biennis L. has not been reported yet. So, the present study is carried out to investigate the effect of water stress and salinity stress under different concentrations i.e, water stress (-0.01 M Pa, -0.03 M Pa, -0.05 M Pa and -0.07 M Pa) and salinity stress (25 mM, 50 mM, 75 mM and 100 mM NaCl) on shoot length, no. of leaves, no. of flowers, no. of nodes, seed yield and root length. At lower water and salinity stress concentrations the Oenothera biennis L. has shown tolerance in terms of morphological features. These findings render Oenothera a sensitive plant at higher stresses concentration. However, changes in characteristics were realistic up to moderate stresses concentration.